Spotlight on the Adolescent’s Mental Health: Distress and Coping amid the COVID-19 Pandemic - Jawed Akbar Dars, Nadeem Iqbal, Zubair Ahmed Khoso, Muhammad Ilyas, Chooni Lal, Nausheen Saifullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: COVID-19 pandemic globally challenged the healthcare sector as well as posed a serious threat to mental health among both young and adults rendering people with a sense of uncertainty and loss. Objective Aim: To assess the psychological burden among the adolescent population during the pandemic and lockdown. Methodology: A cross sectional study was moderated by the research team at the Department of Psychiatry and Behavioral Sciences, Jinnah Postgraduate Medical Center between April 2020 to October 2021. All individuals between the ages of 13 to 17 years were included. The proforma was circulated among residents of the province of Sindh that assessed the emotional symptoms, conduct problems, hyperactivity-inattention, peer relationship problems, and prosocial behaviors among participants. Results: The mean SDQ score was 24.97 with a standard deviation of 6.62. The mean scores for emotional symptoms, conduct problem, hyperactivity, peer problem, and prosocial Scale were 5.47, 6.82, 5.85, 6.82, and 3.02, respectively. A significant relationship was revealed between mental health stability and witnessing a death of a known person due to COVID-19 infection (p=0.003). Furthermore, the study found that Sindhi individuals had significantly higher scores as compared to other ethnic groups (p=0.002). Conclusion: The young population is as equally stressed as adults and may suffer from substantial anxiety during the pandemic. Therefore, parents should be encouraged to create an atmosphere of support and goodwill.